PRINCIPALS OF THE COMPARATIVE GRAMMAR: VERB IN THE SPANISH AND UKRAINIAN LANGUAGES (ASPECT) - Корбозерова, Ніна (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
At the current stage of the development of linguistics, the triple scientific interest is updated towards the theory of the comparison of languages, towards the theory of translation and towards intercultural communication as a consequence of the cardinal changes in the political and cultural life of the society.The important place in translation theory is occupied by grammatical problems. To make the correct grammatical transformations, the translator/interpreter must thoroughly know the similar and distinctive features between the original language and the language of the translation, which is the object of comparative grammar. In general, the grammatical categories adequately reflect the conceptual framework of the world, manifesting its basic invariants.In grammatical categories there are several differences that are the cause of semantic differences in consequence of specific worldviews and particular linguistic world pictures. For example, when comparing the categories and grammatical forms of the Spanish and Ukrainian languages, there is a lot of difference between the number and gender of the suative noun. In addition, in the Spanish language there is the category of determination/indeterminacy that is manifested in the presence/absence of the article, while in the Ukrainian language there is the grammatical case in the noun.The most significant differences between the two languages analyzed are observed in the grammatical categories of the verb, particularly in aspect, tense, mood and voice.__________References:• Vyd dijeslova. Ukrai'ns'ka mova: vid fonetyky do morfologii', https://ukr.ed-era.com>vidi_• Aspecto grammatical, https://es.wikipedia.org>wiki
Keywords: Comparative Grammar, verbal aspect, Spanish, Ukrainian